THE EXPERIENCE OF THAI OLDER ADULTS PARTICIPATING IN LONG-TERM EXERCISE : A QUALITATIVE STUDY - Siriluk Sithichoksakulchai; Santo Imanuel Tonapa; Min-Tao Hsu (Proceeding B-ICON, 2023)
Physical and physiological health declined with age. These reduce activity ability. NCDs are also rising in elderly persons. Thus, increasing older adults’ physical activity reduces sedentary mortality and maintains health. The aim of this study is to explore the experience of Thai older adults participating in long-term exercise. A qualitative design was conducted with individual semi-structured interview online using voice calling via the LINE application. Three older adults aged 72-87. Participants explained their experience with their long-term exercise engagement. Data were analyzed using Colaizzi (1978) method. Four themes emerged from the data collection: (1) receiving support from society, (2) obtaining benefits, (3) understanding ageing demand, and (4) Engaging to be a habit. Motivation to exercise influences older adults' regularity. Extrinsic and intrinsic motivation affect exercise involvement. Older adults gain psychologically and physically from exercise. Personality and society also affect exercise motivation. The findings help older people, healthcare professionals, family members, and society understand geriatric exercise motivation to promote and execute exercise programs.